O PÚBLICO, O PRIVADO E O ESTADO SOB A LÓGICA DO CAPITAL: A EXPANSÃO DO ENSINO SUPERIOR NO SUDOESTE DO PARANÁ - Turmena, Leandro (2009)
of Paraná in the period of 1967 to 2009. The political and economical determinants of the process of expansion of higher education in this region are analyzed, considering the social organization of work (capitalist relationships of production) and the function of the State in the formation of educational politics. The cutting of the object indicates the origin of the first IES (the decade of 1960) and the proliferation of new courses stemming from the 9394/96 Law of the region. Therefore, the survey is epistemologically set in the method of dialectic historic materialism, more specifically in the categories of totality, of contradiction and of mediation. There first was made a contextualization of the Southwest region of Paraná: historical, geographical, political, economical and higher education data (origin and expansion). Next, it moved in the direction of historical development of higher education in Brazil and in the State of Paraná and the function that the State took on in the historical periods determined. Finally, the relationships between the social organization of work, the State reform and the higher education in the decade of 1990 was analyzed. What showed up from the analyses done was that the expansion of higher education in Southwest Paranà starting from the decade, 1990, is articulated dialectically with the form of capitalistic production. The State takes on the administration and the financing of the demands of the society legislating the form of financing of the openings in the private institutions. Thus, contradictorily there was an offer, even though reduced, of public higher education. The survey also showed that the higher education that expands in the logic of the market is the result of the “market of knowledge”, applied to the formation of complex work in order to attend the logic of he “knowledge for the market” under the ideological discourse of development and of employment, which has attracted middle class educational services, though actually having a crisis in this sector. The survey was explicit that the logics of the capital indicate a “development” of the productive forces based on the formation of higher education for the work market and that there is not the development of the survey and the production of knowledge as its main orientation, at least in the investigated region. Above all, it seeks to capacitate workers for the work market and reserves manual labor for minimal qualification. In theory, the formation in higher education, which was actually investigated, has little to contribute for the formation of critical and capable citizens to carry out the political control of the State middle class.